2010
DOI: 10.1107/s0909049509055319
|View full text |Cite
|
Sign up to set email alerts
|

Trace element analysis of hairs in patients with dementia

Abstract: The trace elements of scalp hair samples from > or =60-year-old dementia patients and normal persons have been studied by X-ray absorption near-edge spectroscopy (XANES) in fluorescent mode and wavelength-dispersive X-ray fluorescence spectrometry. Comparisons of hair trace element levels of age-matched dementia patients and normal persons revealed significantly elevated amounts of calcium, chlorine and phosphorus in dementia patients relative to normal persons. The results of XANES measurements identify the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
(35 reference statements)
0
3
0
1
Order By: Relevance
“…X-ray Sulfur detection in human hair fibers (Figure 19) is due to the fact that hair is primarily composed of keratin proteins with a very high content of cysteine, a sulfur-containing amino acid, which commonly forms cystine via a disulfide bond [189,190]. The detection of sulfur in hair by XRF and XANES in dementia has been discussed, for example by Siritapetawee et al [191] in the context of possible roles of calcium, chlorine, phosphorus and sulfur in the etiology of elderly patients' dementia. Also, Inoue et al [189] showed that it is possible to map the oxidation state of cysteine in human hair through Xanes spectroscopy.…”
Section: Frontal Fibrosing Alopeciamentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray Sulfur detection in human hair fibers (Figure 19) is due to the fact that hair is primarily composed of keratin proteins with a very high content of cysteine, a sulfur-containing amino acid, which commonly forms cystine via a disulfide bond [189,190]. The detection of sulfur in hair by XRF and XANES in dementia has been discussed, for example by Siritapetawee et al [191] in the context of possible roles of calcium, chlorine, phosphorus and sulfur in the etiology of elderly patients' dementia. Also, Inoue et al [189] showed that it is possible to map the oxidation state of cysteine in human hair through Xanes spectroscopy.…”
Section: Frontal Fibrosing Alopeciamentioning
confidence: 99%
“…Finally, it is worth noting that various shampoos contain zinc; clinical studies have established that Zn pyrithione is one of the most effective anti-dandruff ingredients in shampoo formulations [189][190][191]196].…”
Section: Frontal Fibrosing Alopeciamentioning
confidence: 99%
“…Additionally, the authors presented their own results by SRXRF to determine the arsenic content in hair samples of patients treated with arsenic trioxide, m-XRF cartography on thin hair slices to obtain distribution maps of As, and m-XANES to verify that inorganic As was incorporated in the hair samples in its trivalent oxidation state. Asian researchers 425 analysed hair samples of patients with dementia using XANES and WDXRF. Elevated amounts of Ca, Cl and P were detected in dementia patients relative to normal persons, but XANES analysis revealed that in both groups the same chemical from was present namely CaCl 2 and PO 4 3À .…”
Section: Clinical and Biologicalmentioning
confidence: 99%
“…1. 緒 言 近年,毛髪に疾病や老化といった,人体の様々な情報が含まれていることが明らかになってきている.例えば アルツハイマー疾病 ,喉頭がん や認知症患者 (Siritapetawee et al, 2010)の 毛髪に含まれる金属元素量が健常者のそれと異なることが報告されている.また乳がん患者の毛髪に含まれるカ ルシウム濃度が頭皮から遠ざかるごとに増加するなど,毛髪の長手方向には過去の身体情報が記録されている可 能性がある .毛髪は加齢によって外形寸法や力学的特性が変化することも報告されている .血液や尿と比較して苦痛が少なく被験者から採取可能な毛髪の様々な情報は,今後,医学, 生物学分野をはじめとする様々な分野で活用される期待が大きい. ところで毛髪は多層構造であって,内部構造が力学的特性 (Yu et al, 2017)や幾何学的特徴 (Tohmyoh et al, 2018) に影響を及ぼすことが知られている.したがって,毛髪の力学的特性は上述の医学診断等において有益な情報を No.20-00043 [DOI: 10.1299/transjsme.20-00043] *1 学生員,東北大学大学院工学研究科ファインメカニクス専攻(〒980-8579 宮城県仙台市青葉区荒巻字青葉 6-6-01) *2 正員,東北大学大学院工学研究科ファインメカニクス専攻 E-mail of corresponding author: tohmyoh@ism.mech.tohoku.ac.jp © The Japan Society of Mechanical Engineers もたらすものと期待できる.これまでに毛髪の力学的特性は引張試験 Yu et al, 2017), 曲げ試験 (曽我部他, 2013;Tohmyoh et al, 2011)やインデンテーション試験 (Wei et al, 2005) Both sides of the rectangular hole were cut to apply the tensile load to the hair sample. ーティクルのはく離面積を算出した.図 9(c)の場合,はく離面積は 47.…”
unclassified